Lockdown lessons: an international conversation on resilient GI science teaching. Issue 1 (2nd January 2022) - Blanford, Justine I.; Bowlick, Forrest; Gidudu, Anthony; Gould, Michael; Griffin, Amy L.; Kar, Bandana; Kemp, Karen; de Róiste, Mairéad; deSabbata, Stefano; Sinton, Diana; Strobl, Josef; Tate, Nicholas; et al.
ABSTRACT: We report the findings from two global panel "conversations" that, stimulated by the exceptional coronavirus pandemic of 2020/21, explored the concept of resilience in geographic science teaching and learning. Characteristics of resilient teaching, both in general and with reference to GISc, are listed and shown to be essentially what might in the past have been called good teaching. Similarly, barriers to resilient teaching are explored and strategies for overcoming them listed. Perhaps the most important conclusion is a widespread desire not to "bounce back" to pre-COVID ways, but to use the opportunity to "bounce forward" towards better teaching and learning practices.